The Unique Significance of the Portrait in the Novel of "Portrait of Dorian Gray" and its Symbolic Expression (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article explores the unique significance of the portrait in Oscar Wilde's novel "The Picture of Dorian Gray" and its profound symbolic expression. The portrait serves as a central metaphor, reflecting the gradual moral decay and corruption of the protagonist, Dorian Gray, while preserving his outward beauty. Through an analysis of the portrait's role, the article delves into themes of vanity, the duality of human nature, and the consequences of a life driven by aestheticism and hedonism. The portrait becomes a powerful symbol of the conflict between appearance and reality, ultimately illustrating the destructive nature of unchecked desires and the moral repercussions of living a life devoid of conscience.